"Rigid body rotation" of the left ventricle in hypoplastic right-heart syndrome: a case from the three-dimensional speckle-tracking echocardiographic MAGYAR-Path Study. (16th June 2014) - Nemes, Attila; Havasi, Kálmán; Forster, Tamás
Abstract Left ventricular twist results from the movement of two orthogonally oriented muscular bands of the helical myocardial structure, with a consequent clockwise rotation of the left ventricular base and counterclockwise rotation of the left ventricular apex. To the best of the authors' knowledge, this is the first time that left ventricular "rigid body rotation", the near absence of left ventricular twist in hypoplastic right-heart syndrome, has been demonstrated.